Time-to-conception and clinical pregnancy rate with a myo-inositol, probiotics, and micronutrient supplement: secondary outcomes of the NiPPeR randomized trial. - Chan S-Y; Barton SJ; Loy SL; Chang HF; Titcombe P; Wong J-T; Ebreo M; Ong J; Tan KM; Nield H; El-Heis S; Kenealy T; et al. (Elsevier B.V., 2023)
Objective To determine whether a combined myo-inositol, probiotics and micronutrient nutritional supplement impacts time-to-natural-conception and clinical pregnancy rates. Design Secondary outcomes of a double-blind randomized controlled trial. Setting Community recruitment. Patients Women aged 18 to 38 years planning to conceive in the United Kingdom, Singapore, and New Zealand, excluding those with diabetes mellitus or receiving fertility treatment. Intervention A standard (control) supplement (folic acid, iron, calcium, iodine, β-carotene), compared with an intervention additionally containing myo-inositol, probiotics, and other micronutrients (vitamins B2, B6, B12, D, zinc). Main Outcome Measures Number of days between randomization and estimated date of natural conception of a clinical pregnancy, as well as cumulative pregnancy rates at 3, 6, and 12 months. Results Of 1729 women randomized, 1437 (83%; intervention, n=736; control, n=701) provided data. Kaplan-Meier curves of conception were similar between intervention and control groups; the time at which 20% achieved natural conception was 90.5 days (95% confidence interval: 80.7, 103.5) in the intervention group compared with 92.0 days (76.0, 105.1) in the control group. Cox's proportional hazard ratios (HRs) comparing intervention against control for cumulative achievement of pregnancy (adjusted for site, ethnicity, age, body mass index, and gravidity) were similar at 3, 6, and 12 months. Among both study groups combined, overall time-to-conception lengthened with higher preconception body mass index, and was longer in non-White than in White women. Among women who were overweight the intervention shortened time-to-conception compared with control regardless of ethnicity (12-month HR=1.47 [1.07, 2.02], P=.016; 20% conceived by 84.5 vs. 117.0 days) and improved it to that comparable to nonoverweight/nonobese women (20% conceived by 82.1 days). In contrast, among women with obesity, time-to-conception was lengthened with intervention compared with control (12-month HR=0.69 [0.47, 1.00]; P=.053; 20% conceived by 132.7 vs. 108.5 days); an effect predominantly observed in non-White women with obesity. Conclusions Time-to-natural-conception and clinical pregnancy rates within a year were overall similar in women receiving the intervention supplement compared with control. Overweight women had a longer time-to-conception but there was suggestion that the supplement may shorten their time-to-conception to that comparable to the nonoverweight/nonobese women. Further studies are required to confirm this. Clinical Trial Registration Number clinicaltrials.gov (NCT02509988)
Keywords: NiPPeR trial; fecundability; fertility; nutritional supplement; preconception; Pregnancy; Humans; Female; Pregnancy Rate; Overweight; Dietary Supplements; Inositol; Probiotics; Micronutrients; Double-Blind Method; Obesity